A methylammonium iodide healing method for CH3NH3PbI3 perovskite solar cells with high fill factor over 80%. (November 2021) - Li, Zhen; Yang, Guanjun
Abstract: Repressing the thermal decomposition during the process of heat treatment plays an indispensable part in the preparation of perovskite films. Here, a methylammonium iodide healing method was applied to prevent the volatilization of the organic component inside the perovskite structure during the heat treatment. High-quality CH3 NH3 PbI3 film with a much larger grain size over 800 nm was successfully fabricated via this healing method. Besides, the absorption and photoluminescence intensity were also both improved. Finally, the best power conversion efficiency of 18.89% with a fill factor over 80% was realized in an n–i–p configuration while possessing outstanding stability. This work suggests that methylammonium iodide healing method is a reliable way to promote crystal growth and improve the photovoltaic performance and humidity stability of the CH3 NH3 PbI3 solar cells.